(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article substantiates the need to search for the most convenient methods for achieving the best results in mastering the English language by students within the framework of interdisciplinary relations.